2002
DOI: 10.1210/jcem.87.3.8326
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptors in Human Luteinized Granulosa Cells: Activation Blocks Gap Junctions and Induces the Transcription Factor Early Growth Response Factor-1

Abstract: Acetylcholine (ACh) was recently described to be produced by and act on human luteinizing granulosa cells (GCs). Cholinergic agents increase intracellular calcium levels and stimulate GC proliferation via muscarinic receptors. Based on this observation and because endocrine cells of the forming human corpus luteum (CL), which are the in vivo counterparts of GCs, also proliferate in vivo, we hypothesized that ACh may be a factor involved in the regulation of the complex cellular events occurring during ovulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…There is evidence that the expression of voltage-activated Ca 2ϩ channels undergoes dynamic changes during cell proliferation and differentiation (22)(23)(24). Because human GCs in culture are dynamic cells, which also proliferate (45) and differentiate, it is possible that the expression of isoforms of Ca 2ϩ channels is confined to certain phases of the cell cycle and/or differential stages. Our study, in which GCs were treated with hCG, further suggested this possibility and indicated regulation of Ca 2ϩ channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the expression of voltage-activated Ca 2ϩ channels undergoes dynamic changes during cell proliferation and differentiation (22)(23)(24). Because human GCs in culture are dynamic cells, which also proliferate (45) and differentiate, it is possible that the expression of isoforms of Ca 2ϩ channels is confined to certain phases of the cell cycle and/or differential stages. Our study, in which GCs were treated with hCG, further suggested this possibility and indicated regulation of Ca 2ϩ channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the pancreas, ACh increases paracellular permeability by interfering with tight junctions ( Jansen et al ., 1980 ). mAChRs affect the activity of gap junctions in gastric epithelial cells (rat) and in granulosa cells of the ovary ( Ueda et al ., 1995 ; Fritz et al ., 2002 ), most likely an extremely old regulatory target on the evolutionary timescale. Very recently it has been demonstrated that ACh is the transmitter responsible for regulating gap‐junction activity of the central synapse of Drosophila ( Allen and Murphey, 2007 ).…”
Section: Cellular Functions Of Non‐neuronal Achmentioning
confidence: 99%
“…Acetylcholine has been reported to be a mitogen in various cell types (Ashkenazi et al, 1989;Guizzetti et al, 1996;Luthin et al, 1997;Rayford et al, 1997;Guizzetti et al, 1998;Metzen et al, 2003). Furthermore, stimulation of M 3 and M 5 mAChRs in human luteinized granulosa cells increased intracellular Ca + + concentrations and resulted in an increase of cell proliferation (Fritz et al, 1999(Fritz et al, , 2001, gap junctions communication and regulation of gene expression were also affected (Fritz et al, 2002). Thus, the effect of carbachol on Sertoli cells proliferation points out for physiological significance and opens questions that remain to be answered such as the effect of carbachol in the pattern of protein expression secreted by Sertoli cells and/or in the modulation of gap junctions communication.…”
Section: Discussionmentioning
confidence: 99%